Analisis Proksimat dan Total Serat Pangan pada Crackers Fortifikasi Tepung Tempe dan Koleseom (Talinumtiangulare) - Hermawan Seftiono; Evelyn Djiuardi; Sherly Pricila (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Kolesom is a vegetable which contains a high dietary fiber content. Tempe is an Indonesian food that contains high protein and can be an alternative protein source. However, both tempe and kolesom haven’t been widely utilized. One way to improve the utilization is by adding kolesom and tempe flour to increase the nutrient content of crackers. Crackers are one type of crunchy-textured biscuits and are often consumed as a snack. The addition of tempe flour and kolesom flour are also expected to increase protein and dietary fiber content of crackers. This research was aimed to determine the best formulation and proximate level of crackers fortified with tempe and kolesom flour. Cracker production began with the manufacture of tempe flour which has a protein content of 49.08% and kolesom flour which has a total dietary fiber content of 19.22%. Determination of the best crackers based on panelists’ preferences was based on organoleptic test. The highest overall percentage of preference was found in F5 crackers (T10% + K2.5g), containing 4.81% moisture content, 2.53% ash content, 18.43% total fat, 11.90% protein, 62.33% total carbohydrate, and total dietary fiber 8.29 %.